The effectiveness and safety of staged halo-pelvic traction combined with posterior spinal fusion in the treatment of severe rigid spine deformity: a prospective cohort study - Lijin Zhou; Honghao Yang; Jianqiang Wang; Yiqi Zhang; Yunsheng Wang; Yong Hai (Journal of Orthopaedic Surgery and Research)
Abstract Background Severe rigid spinal deformities present significant challenges in correction surgery due to complexity and associated comorbidities. To mitigate the surgical risks, preoperative halo-pelvic traction (HPT) have been employed. This study aims to evaluate the effectiveness and safety of staged HPT combined with posterior spinal fusion (PSF) in the treatment of severe rigid spine deformity. Methods This is a prospective cohort study. From 2020 to 2022, 61 consecutive patients (mean age 26.2 years) with severe rigid spine deformity who underwent staged HPT combined with PSF with a minimum 24-month follow-up were recruited. Radiographic parameters, clinical information, pulmonary functions tests, and perioperative complications were recorded. Results The mean preoperative coronal Cobb angle was 114.2° ± 38°, and the mean MK was 105.8° ± 34.7°. Following the HPT ( mean duration 19.2 weeks), the mean coronal Cobb angle were corrected to 55.3° post-traction (50.6%) and 47.4° after PSF (58.3%); the mean MK angle were corrected to 52.6° post-traction (49.5%) and 38.1° after PSF (63.4%). The overall complication rate during HPT was 16.4%, while surgery-related complications were 18.0%, with no permanent neurological deficits observed. Conclusion Staged HPT combine with PSF is effective and safe for patients with severe rigid spine deformities. HPT could mitigate the severity of spine deformity, minimize the need for invasive three-column osteotomies, and reduce the risk of complications for correction surgery.